The Sufism, Human Solidarity, and Social Emancipation in Caste-Based Societies in South Asia - Cahaya Mulyani Sakti; Mohammad Izdiyan Muttaqin; Mulawarman Umer Dar; Saadiya Tahreem; Mulawarman Hannase (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study critically examines how Sufism, as the esoteric dimension of Islam, functions—and is contested—as a form of emancipatory praxis fostering human solidarity within hierarchically structured societies in South Asia. Historically, Sufism has contributed to the formation of spiritual and social spaces that potentially transcend religious, ethnic, and caste boundaries. Within Hindu-influenced cultural contexts marked by inherited caste stratification, Sufi teachings articulate an alternative ethical paradigm grounded in tawḥīd, rearticulated as a theological critique of caste hierarchy, religious elitism, and social stratification, alongside principles of universal love (maḥabbah). Drawing on Paulo Freire’s theory of social emancipation and Asghar Ali Engineer’s Islamic liberation theology, this study employs a qualitative critical approach To analyze both the emancipatory potential and structural limitations of Sufism as a humanistic practice. The analysis focuses on Sufi shrines, devotional practices, and inter-communal interactions as sites in which equality and solidarity are negotiated within everyday social life. The findings suggest that while Sufi praxis can generate inclusive spaces and foster critical awareness among marginalized communities, its emancipatory capacity remains contingent upon broader power relations, socio-economic inequalities, and the institutionalization of spiritual authority. Studi ini secara kritis mengkaji bagaimana Sufisme, sebagai dimensi esoteris Islam, berfungsi—dan sekaligus diperdebatkan—sebagai suatu bentuk praksis emansipatoris yang menumbuhkan solidaritas kemanusiaan dalam masyarakat Asia Selatan yang terstruktur secara hierarkis. Secara historis, Sufisme telah berkontribusi pada pembentukan ruang-ruang spiritual dan sosial yang berpotensi melampaui batas-batas agama, etnis, dan kasta. Dalam konteks kebudayaan yang dipengaruhi oleh tradisi Hindu dan ditandai oleh stratifikasi kasta yang diwariskan, ajaran-ajaran Sufi merumuskan suatu paradigma etis alternatif yang berlandaskan pada tawḥīd, yang direartikulasi sebagai kritik teologis terhadap sistem kasta, elitisme keagamaan, dan hierarki sosial, serta didukung oleh prinsip cinta universal (maḥabbah). Dengan merujuk pada teori emansipasi sosial Paulo Freire dan teologi pembebasan Islam Asghar Ali Engineer, studi ini menggunakan pendekatan kualitatif-kritis untuk menganalisis baik potensi emansipatoris maupun keterbatasan struktural Sufisme sebagai praktik humanistik. Analisis difokuskan pada makam-makam suci Sufi, praktik-praktik devosional, dan interaksi antar-komunitas sebagai arena tempat nilai-nilai kesetaraan dan solidaritas dinegosiasikan dalam kehidupan sosial sehari-hari. Temuan penelitian menunjukkan bahwa meskipun praksis Sufi mampu menciptakan ruang-ruang inklusif dan menumbuhkan kesadaran kritis di kalangan komunitas yang terpinggirkan, kapasitas emansipatorisnya tetap bergantung pada relasi kuasa yang lebih luas, ketimpangan sosial-ekonomi, serta proses institusionalisasi otoritas spiritual.